Dermatoglyphic patterns of goitrous children in endemic iodine deficiency area - Martira Maddeppungeng; R Satriono (Paediatrica Indonesiana, 2004)
Background Goiter mapping on elementary school students in1998 showed that the prevalence of endemic goiter was still highat Enrekang regency, South Sulawesi despite various programs tomanage this problem. This raised questions if there were any otherfactors that contribute to the occurrence of goiter e.g. genetic fac-tor, which can be assessed indirectly by dermatoglyphic pattern.Objective To determine the dermatoglyphic pattern in goitrouschildren and compare it to normal children.Methods A cross sectional study was done to investigate the cor-relation between goiter and dermatoglyphic patterns on 115 el-ementary school students at Anggeraja and Baraka subdistricts,Enrekang regency. Dermatoglyphic patterns of finger tips of bothhands and right hallux were scanned using Prolink scanner withMaximum Resolution of 19200x19200dpi and interpreted usingphoto/image editing computer program.Results Seventy two (62.6%) of 115 children were goitrous, sev-enty (97%) were of stage1, and 2 (3%) of stage 2. No significantdifference was found in dermatoglyphic patterns between normaland goitrous children. Tibial loop pattern of the right hallux tendedto be more frequent in goitrous children than that of normal chil-dren, but it was not statistically different (in level of significancy of0.05) compared to normal children (p=0.085).Conclusions This study indicates that the possibility of the role of ge-netic factor in the development of goiter in endemic area is unlikely